2021
DOI: 10.1111/ijfs.15057
|View full text |Cite
|
Sign up to set email alerts
|

Addition of waxy, low‐ or high‐amylose rice starch differentially affects microstructure, water migration, texture and cooking quality of dried potato starch noodles

Abstract: Potassium alum (PA) is commonly used as an improver for quality of potato starch noodles (PSN). However, PA poses health risks to consumers, thus making it imperative to seek substitutes for Al3+. In this study, effects of rice starch addition on quality of PSN were investigated. Scanning electron microscopy revealed that addition of low‐amylose rice starch (LARS) or 40% waxy rice starch (WRS) enhanced structural development of PSN. Magnetic resonance imaging showed that the presence of LARS increased water re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
4
1
Order By: Relevance
“…However, OCT was found to have a strong negative correlation with both turbidity and cooking loss, such that upon the addition of porous starch, with a decrease in optimum cooking time, an increase in cooking loss was witnessed. This contradicts the observations made by Wang et al [ 47 ] and Liu et al [ 48 ], where a prolonged cooking time resulted in an increased cooking loss. Although the cooking loss was well within the acceptable limits of 10%, porous starch weakened the gluten network, causing solid matter to leach into the cooking water.…”
Section: Resultscontrasting
confidence: 87%
“…However, OCT was found to have a strong negative correlation with both turbidity and cooking loss, such that upon the addition of porous starch, with a decrease in optimum cooking time, an increase in cooking loss was witnessed. This contradicts the observations made by Wang et al [ 47 ] and Liu et al [ 48 ], where a prolonged cooking time resulted in an increased cooking loss. Although the cooking loss was well within the acceptable limits of 10%, porous starch weakened the gluten network, causing solid matter to leach into the cooking water.…”
Section: Resultscontrasting
confidence: 87%
“…Odabas et al ( 2022 ) reported that the hardness and chewiness of gluten‐free noodles increased with an increase in the percentages of quinoa and yellow lentil flour and peaked at the highest levels of incorporation (50%). Liu et al ( 2021 ) found that low‐amylose rice starch significantly increased the tensile strength and hardness of potato starch noodles, whereas waxy rice starch had the reverse effect. Waliullah et al ( 2021 ) reported that the textural properties of starch noodles could be improved by ultrafine sweet potato residues.…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al (2021) found that low-amylose rice starch significantly increased the tensile strength and hardness of potato starch noodles, whereas waxy rice starch had the reverse effect Waliullah et al (2021). reported that the textural properties of starch noodles could be improved by ultrafine sweet potato residues.…”
mentioning
confidence: 99%
“…Consumption of potatoes may reduce the incidence of certain diseases including diabetes, atherosclerosis and cancer (Xu et al ., 2020). Therefore, potato flour is now often added to innovative foods, such as gluten‐free foods, as a way to improve the quality of the diet and prevent disease (Liu et al ., 2021a,b; Lu et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It is also rich in minerals such as Mg, Zn, Cu and Si. It has an alkaline pH, which helps to maintain the body’s acid–base balance and is rich in vitamin C. The nutrition of potato flour is more comprehensive than rice flour and can be mixed with coarse grain flour and highly refined rice flour to achieve complementary advantages (Liu et al ., 2021a,b; Ricardo et al ., 2021). In addition, its water absorption, water‐holding capacity and pasting properties are better than rice starch.…”
Section: Introductionmentioning
confidence: 99%